1987
DOI: 10.2307/1242279
|View full text |Cite
|
Sign up to set email alerts
|

Time and the Recreational Demand Model

Abstract: In this paper, a theoretically consistent approach to including time costs in recreational demand models is developed. The demand model is conditional on the recreationist's labor market situation. For individuals at corner solutions in the labor market, utility maximization is subject to two constraints, leading to a demand function with travel costs and travel time as independent variables. With interior solutions in the labor market, time is valued at the wage rate and combined with travel costs to produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
146
0
6

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 212 publications
(152 citation statements)
references
References 13 publications
0
146
0
6
Order By: Relevance
“…An increasing proportion of the population being overweight or obese in most Western 2 societies is leading to a significant burden on society and contributing to the rise of 3 conditions such as diabetes, cardiovascular disease and cancer (James et al, 2004; WHO, 4 2011). Physical activity levels are on the decline in Northern Ireland, as in other countries, 5 including England, (Farrell et al, 2013, SportNI, 2010, with 60% of the local adult population 6 not meeting the recommended levels of activity (DHSSPS, 2011).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…An increasing proportion of the population being overweight or obese in most Western 2 societies is leading to a significant burden on society and contributing to the rise of 3 conditions such as diabetes, cardiovascular disease and cancer (James et al, 2004; WHO, 4 2011). Physical activity levels are on the decline in Northern Ireland, as in other countries, 5 including England, (Farrell et al, 2013, SportNI, 2010, with 60% of the local adult population 6 not meeting the recommended levels of activity (DHSSPS, 2011).…”
mentioning
confidence: 99%
“…23 Walking is the most common form of moderate-intensity physical activity among adults 1 (Siegel et al, 1995;Eyler et al, 2003;Ogilvie et al, 2007;Sport NI, 2010), is widely accessible 2 and especially appealing to obese people, who are less likely to perform vigorous-intensity 3 physical activity (Erlichman et al, 2002). It is an aerobic exercise that confers the diverse 4 health benefits of physical activity with few adverse effects (Morris and Hardman, 1997). 5 Several studies have confirmed that walking reduces the development of cardiovascular Many factors influence or facilitate the choice to walk for either travel or recreational 10 purposes, including the availability of footpaths, the attractiveness of the route (e.g.…”
mentioning
confidence: 99%
See 3 more Smart Citations